Identification of genes preferentially expressed in wild strawberry receptacle fruit and demonstration of their promoter activities - Rachel Shahan; Dongdong Li; Zhongchi Liu (Horticulture Research, 2019)
A fruitful investigation of strawberry production A newly-acquired collection of gene regulatory elements gives researchers a powerful toolbox for studying fruit production in strawberry plants. Tissue-specific gene expression is governed by DNA sequences known as promoters, and researchers led by Rachel Shahan and Zhongchi Liu at the University of Maryland recently set out to identify promoters that regulate the initiation of strawberry formation. Most fruits form in the plant ovary, but strawberries originate from the same ‘receptacle’ structure that gives rise to flowers. Liu and Shahan therefore used RNA sequencing to identify genes that are expressed specifically in this tissue but not elsewhere in the strawberry plant. Their efforts uncovered seven promoters that appear to operate in a highly receptacle-specific fashion. Armed with these sequences, researchers can now begin to manipulate and thereby dissect the genetic mechanisms governing strawberry fruit formation.